Self home blood pressure monitoring in pregnancy: how reliable is it? - L., Hemapriya; Desai, Nagaraj; Bhandiwad, Ambarish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The use of automated blood pressure monitors in pregnancy has become increasingly popular, as more women tend to get involved in their healthcare. Not only does it reduce clinician visits, it also helps to eliminate the white coat hypertension. Methods: We conducted a prospective study in the antenatal department of JSS Medical College and Hospital, Mysuru; over a period of one year, from July 2016 to June 2017. The blood pressures of 50 women were recorded at four different periods of gestation using the conventional ‘Diamond mercury Sphygmomanometer’ versus the automated ‘Omron HEM 7130’ home BP monitor and compared. Results: The recordings of systolic blood pressure at home were consistently less than the office measurements at all periods of gestation. However, the difference was not statistically significant. The comparison of diastolic pressures revealed minimal variations between the mean of the office and home blood pressure recordings. The mean arterial pressure also revealed a similar trend. Conclusions: Self-monitoring of blood pressure is a feasible and acceptable option to pregnant women. It might make antenatal care more effective, but we need further research to establish safety and efficacy, the impact on women and health professionals, and how best to use the results.